2022
DOI: 10.1029/2021jf006580
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Cosmogenic Nuclides Approach for Determining the Temperature‐Dependence of Erosion

Abstract: Physical weathering in cold, steep bedrock hillslopes occurs at rates that are thought to depend on temperature, but our ability to quantify the temperature‐dependence of erosion remains limited when integrating over geomorphic timescales. Here, we present results from a 1D numerical model of in‐situ cosmogenic 10Be, 14C, and 3He concentrations that evolve as a function of erosion rate, erosion style, and ground surface temperature. We used the model to explore the suitability of these nuclides for quantifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…Previously, paired 14 C-10 Be studies were hampered by the difficulty of measuring in situ 14 C (e.g., Lifton et al, 2001;Pigati et al, 2010), but recent advances in 14 C extraction techniques make utilizing this nuclide more feasible (e.g., Lifton et al, 2015;Lupker et al, 2019). As a consequence, several new studies using paired 14 C-10 Be have identified complex erosional histories (e.g., Hippe et al, 2012Hippe et al, , 2019Hippe et al, , 2021Kober et al, 2019) and explored emerging applications (Dennis & Scherler, 2022;Schimmelpfennig et al, 2021). However, efforts to understand non-steady-state sediment transport dynamics from paired 14 C-10 Be are still in their infancy (e.g., Hippe, 2017;Hippe et al, 2019Hippe et al, , 2021, and to date few studies have utilized this pairing in high-relief, mountainous terrain (Dennis & Scherler, 2022;Kober et al, 2012Kober et al, , 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, paired 14 C-10 Be studies were hampered by the difficulty of measuring in situ 14 C (e.g., Lifton et al, 2001;Pigati et al, 2010), but recent advances in 14 C extraction techniques make utilizing this nuclide more feasible (e.g., Lifton et al, 2015;Lupker et al, 2019). As a consequence, several new studies using paired 14 C-10 Be have identified complex erosional histories (e.g., Hippe et al, 2012Hippe et al, , 2019Hippe et al, , 2021Kober et al, 2019) and explored emerging applications (Dennis & Scherler, 2022;Schimmelpfennig et al, 2021). However, efforts to understand non-steady-state sediment transport dynamics from paired 14 C-10 Be are still in their infancy (e.g., Hippe, 2017;Hippe et al, 2019Hippe et al, , 2021, and to date few studies have utilized this pairing in high-relief, mountainous terrain (Dennis & Scherler, 2022;Kober et al, 2012Kober et al, , 2019.…”
mentioning
confidence: 99%
“…As a consequence, several new studies using paired 14 C-10 Be have identified complex erosional histories (e.g., Hippe et al, 2012Hippe et al, , 2019Hippe et al, , 2021Kober et al, 2019) and explored emerging applications (Dennis & Scherler, 2022;Schimmelpfennig et al, 2021). However, efforts to understand non-steady-state sediment transport dynamics from paired 14 C-10 Be are still in their infancy (e.g., Hippe, 2017;Hippe et al, 2019Hippe et al, , 2021, and to date few studies have utilized this pairing in high-relief, mountainous terrain (Dennis & Scherler, 2022;Kober et al, 2012Kober et al, , 2019.…”
mentioning
confidence: 99%